Analisis Kebutuhan Air Domestik Daerah Aliran Sungai Kampar (Studi Kasus: Pos AWLR Danau Bingkuang) - Al-Khani, M. Rizki; Fauzi, Manyuk; Lilis, Yohanna (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The Watershed Kampar AWLR Danau Bingkuang (DAS) is a watershed located in the Kampar Regency. The watershed Kampar AWLR Danau Bingkuang has an area of 669.99 km2. Water resource problems occur during the dry season, this watershed experiences drought, while in the rainy season the water discharge will increase and cause flooding. The population in the Kampar river basin has increased every year. This increase in population also increases the amount of domestic water demand. In 2010 domestic water demand was 25,157.6 m3/day, in 2019 it was 34,398.9 m3/day. Meanwhile, the projection for domestic water demand in the next 20 years is 54,935.11 m3/day. Keywords: Danau Bingkuang, Watershed, Domestic Water Needs